Impact of natural capital loss on poverty in the Yucatán Peninsula, Mexico: a synthetic control analysis - Avilés-Polanco, Gerzaín; Beltrán-Morales, Luis Felipe; Sour, Laura; Hernández-Trejo, Víctor; Martinez-Cruz, Adan L.; Ortega-Rubio, Alfredo (Frontiers in Environmental Science, 2025)
This study explores the relationship between natural capital, environmental policies, and poverty alleviation, with a focus on the Yucatán Peninsula in Mexico. Utilizing analytical techniques such as the Synthetic Control Method, the research assesses the causal impact of natural capital loss—estimated at 14.29% between 2018 and 2022—on multidimensional poverty levels. Findings indicate that the decline in natural resources has contributed to a roughly 2% increase in poverty, preventing approximately 232,150 individuals from escaping impoverishment. The construction of infrastructure projects like the Mayan Train has significantly contributed to natural resource depletion. Despite ongoing social policies—including social programs and infrastructure investments—these efforts have been partially offset by ecological degradation, underscoring the importance of integrating ecological considerations into development strategies. The study emphasizes that conserving natural capital is vital for sustainable development and social wellbeing, advocating for policies that balance economic growth with ecological preservation. Incorporating ecological metrics, such as the natural capital index, into poverty assessments can enhance policy effectiveness. Overall, the findings underscore that environmental conservation is essential for effective poverty reduction, urging policymakers to adopt integrated approaches that prioritize ecological health alongside social and economic objectives for sustainable development.